181 the acquisition of English negative constructions by a Malay bilingual child - Khazriyati Salehuddin, (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2012)
The English negative construction is one of the most difficult constructions to be mastered in the process of acquiring the English Language due to the fact that such a construction involves both morphological and syntactic aspects of the language. The morphology and syntax of children’s English negative constructions have been extensively studied both on native speakers and non-native speakers of the English language. However, to this date, no such studies have been conducted on Malay children who are acquiring English simultaneously with the acquisition of their mother tongue. This manuscript presents an investigation on the acquisition of English negative constructions of a Malay girl who was acquiring English at the same time as she was acquiring Malay. Results indicate that, to a certain extent, there is a resemblance in the production of negative constructions between children who were native speakers of English and the subject. Yet, the difference in the acquisition pattern is intriguing. Hence, this manuscript concludes with possible explanations to the cross-linguistic discrepancy in the acquisition pattern of the English negative constructions.